2017
DOI: 10.1080/17476348.2017.1358619
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation for the treatment of obstructive sleep apnoea: a review of the evidence

Abstract: Obstructive sleep apnoea is an increasingly prevalent clinical condition with significant impact on individuals and public health. Continuous positive airway pressure therapy is the standard treatment, but adherence is limited and alternative treatments are needed. In this context, non-invasive and invasive methods for the electrical stimulation of upper airway dilator muscles have been demonstrated to be effective in selected patients. Areas covered: This review will cover investigations on the clinical effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 80 publications
0
24
0
1
Order By: Relevance
“…Interface-related problems were reduced when patients used BPAP and did not impact adherence to the same extent as with CPAP. CPAP is the first-line therapy for moderate-severe OSA but second-line alternatives such as MAD for mild OSA, BPAP for moderate-severe OSA (with significant co-morbidity) and, experimentally, the use of electrical stimulation need to be considered when first-line therapy is not successfully employed 12 to address specific features of the phenotypically different OSA patients. 21 Previous studies have shown that BPAP and CPAP therapies can achieve similar efficacy in controlling OSA, 17,22 but these studies did not focus on patients requiring high pressures to achieve control of OSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interface-related problems were reduced when patients used BPAP and did not impact adherence to the same extent as with CPAP. CPAP is the first-line therapy for moderate-severe OSA but second-line alternatives such as MAD for mild OSA, BPAP for moderate-severe OSA (with significant co-morbidity) and, experimentally, the use of electrical stimulation need to be considered when first-line therapy is not successfully employed 12 to address specific features of the phenotypically different OSA patients. 21 Previous studies have shown that BPAP and CPAP therapies can achieve similar efficacy in controlling OSA, 17,22 but these studies did not focus on patients requiring high pressures to achieve control of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether bilevel positive airway pressure (BPAP) could be an effective second-line therapy in this cohort of patients and found that BPAP significantly improved adherence and symptom control when compared to CPAP. specialist treatment should include assessment and guidance of suitable patients through an established treatment algorithm 12 to select the best second-line therapy if CPAP is not tolerated.…”
Section: Summary At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…82 Although some contradictory results have been published in the past, the last evidences are promising in terms of treatment efficacy and tolerability. 83 In the future, new technical advances and the device refinement are expected in order to better define the role of the transcutaneous stimulation in the treatment of OSA.…”
Section: Future Developments: Transcutaneous Nerve Stimulationmentioning
confidence: 99%
“…Different approaches to use electrical stimulation to activate the upper airway dilator muscles have been reported to enhance airway patency in OSA (51)(52)(53)(54)(55). Pengo et al investigated the impact and feasibility of overnight bilateral submental transcutaneous electrical stimulation in OSA in the first randomised sham-controlled double-blind trial in 36 patients [mean age 50.8 (SD ±11.2) years, 83.3% male, median BMI 29.6 (IQR 26.9-34.9) kg/m 2 , ESS score 10.5 (4.6) points, ODI median 25.7 (IQR 16.0-49.1)/hour and AHI median 28.1 (IQR 19.0-57.0)] (54).…”
Section: Transcutaneous Electrical Stimulation/hypoglossal Nerve Stimmentioning
confidence: 99%